STRUCTURE OF THE GASTROPODS COMMUNITY IN THE COASTAL WATERS OF DOMBA, PANDEGLANG REGENCY, BANTEN - Debby Aurelia; Donny Juliandri Prihadi; Lintang Permata Sari Yuliadi; Yuniarti Yuniarti; Sabrina Silvi Asyifa; Esther Rosida Gultom; Loise Regina (Universitas Mataram, 2025)
Marine gastropods play an important role in marine ecosystems as one of the parameters thatcan be used to assess the health of the marine environment. The waters of Domba Beach havea fairly important aquatic community, namely the gastropod community. This study wasconducted in the waters of Domba Beach, Pandeglang Regency, Banten, with the aim ofdetermining the abundance of gastropod species and the structure of the gastropod community,including the diversity index, evenness index, and dominance index of gastropods. Gastropoddata sampling was conducted using the quadrant line transect method with a quadrant size of50x50 cm on 11 transects. A total of 19 gastropod species were found, consisting of 12 familiesand 17 genera. The gastropod with the highest abundance was the species Clypeomorusbifasciata. Meanwhile, the species with the lowest abundance were Conus ebraeus, Cymatiummuricinum, Neverita didyma, and Nerita albicilla. The average diversity index (H’) ofgastropods at the study site was 2.42, the evenness index (E) was 0.82, and the dominanceindex (D) was 0.12. This indicates that the gastropod community structure in the seagrassecosystem of Domba Beach is moderate with high evenness and no dominant species.